The role of HDL on plaque stabilization and regression: basic mechanisms and clinical implications - Feig, Jonathan E. (Coron Artery Dis, 2016)
Based on studies that extend back to the early 1900s, regression and stabilization of atherosclerosis in humans has gone from a concept to one that is achievable. Successful attempts at regression generally applied robust measures to improve plasma lipoprotein profiles. Possible mechanisms responsible for lesion shrinkage include decreased retention of atherogenic apolipoprotein B within the arterial wall, efflux of cholesterol and other toxic lipids from plaques, emigration of lesional foam cells out of the arterial wall, and influx of healthy phagocytes that remove necrotic debris as well as other components of the plaque. Currently available clinical agents, though, still fail to stop most cardiovascular events. For years, HDL has been considered the “good cholesterol.” Clinical intervention studies to causally link plasma HDL-C levels to decreased progression or to the regression of atherosclerotic plaques, are relatively few because of the lack of therapeutic agents to selectively and potently raise HDL-C. The negative results of studies that were performed have casted uncertainty as to the role HDL possesses in terms of atherosclerosis. It is becoming clearer, though, that HDL function rather than quantity is most crucial and therefore, discovering agents that enhance the quality of HDL should be the goal.